2019
DOI: 10.1186/s12968-019-0553-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress increases intracardiac 4D flow cardiovascular magnetic resonance -derived energetics and vorticity and relates to VO2max in Fontan patients

Abstract: Background We hypothesize that dobutamine-induced stress impacts intracardiac hemodynamic parameters and that this may be linked to decreased exercise capacity in Fontan patients . Therefore, the purpose of this study was to assess the effect of pharmacologic stress on intraventricular kinetic energy (KE), viscous energy loss (EL) and vorticity from four-dimensional (4D) Flow cardiovascular magnetic resonance (CMR) imaging in Fontan patients and to study the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Axial contrast-enhanced T1-W gradient echo sequence (n) and T2-weighted sequence (o) reveal a slightly enlarged liver with peripheral enhancement pattern and perisinusoidal sparing, consistent with liver congestion in clinical use in a few institutions and require specific software analysis tools (Fig. 8) [37][38][39]. MR strain analysis and feature tracking are, like echocardiography, newer techniques that are garnering more attention to how diastolic and systolic function perform in the single-ventricle circulation and also in pediatric patients [28,34].…”
Section: Imaging In Cardiovascular Complicationsmentioning
confidence: 81%
“…Axial contrast-enhanced T1-W gradient echo sequence (n) and T2-weighted sequence (o) reveal a slightly enlarged liver with peripheral enhancement pattern and perisinusoidal sparing, consistent with liver congestion in clinical use in a few institutions and require specific software analysis tools (Fig. 8) [37][38][39]. MR strain analysis and feature tracking are, like echocardiography, newer techniques that are garnering more attention to how diastolic and systolic function perform in the single-ventricle circulation and also in pediatric patients [28,34].…”
Section: Imaging In Cardiovascular Complicationsmentioning
confidence: 81%
“…Vorticity refers to the local spinning of blood particles and numerous factors may affect the generation of vorticity including flow velocity gradients and flow directionality. The increase in vorticity can lead to favorable effects such as conservation of momentum by KE storage but also some adverse effects when the optimal flow direction is disturbed due to abnormal intra-cardiac structures [26]. Previously, this hemodynamic parameter was found to be associated with ventricular diastolic dysfunction in different clinical settings and reduced LV vorticity values were observed in patients with chronic obstructive pulmonary disease [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Furthermore, dobutamine stress MRI has shown to increase systolic kinetic energy in the Fontan circulation, and a larger kinetic energy increase was associated with markers of reduced exercise tolerance. 21 It has been suggested that increased systolic peak kinetic energy indicates a lower efficiency in the cardiac circulation, as there is a higher workload required to pump a lower volume of blood. 20 This higher systolic kinetic energy in the ventricle may also be a marker for ventricular dysfunction.…”
Section: Systolic Kinetic Energymentioning
confidence: 99%